Fabrication of a Novel Fe3O4/BiOCl Nanocomposite as Magnetic Visible Light Photocatalytic Materials - Bai, Jingyi; Zhao, Rongfang; Diao, Guowang (Current Nanoscience, 2015)
A magnetic Fe3O4/BiOCl nanocomposite has been prepared by a facile deposition–precipitation process. The microstructure and morphology of this nanocomposite were performed by transmission electron microscopy (TEM), high-resolution TEM (HRTEM) and X-ray diffraction (XRD). The Fe3O4/BiOCl magnetic nanocomposite displays excellent catalytic activity for the photodegradation of RhB under simulated solar light irradiation. Introducing the magnetic materials Fe3O4 in the nanocomposite makes the Fe3O4/BiOCl nanocomposite photocatalyst easily being reused without loss of activity due to its magnetic property. The excellent activity, photo-stability and magnetic recyclability of the nanocomposite photocatalyst reveal that it is a promising candidate for environmental remediation.
Keywords: BiOCl